(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article provides information about Sayed Muhammad Rahim Khan Soniy, one of the major Khans of the qongot dynasty, who ruled the Khiva Khanate by the author. The events of his reign in the Khiva Khanate are considered.